Peran Perguruan Tinggi Pesantren dalam Implementasi Literasi Ekonomi - Ahmad Lukman Nugraha; Adib Susilo; Chaerul Rochman (Universitas Pembangunan Nasional Veteran Jakarta, 2021)
AbstractThis study aims to determine the role of Islamic boarding schools in the application of economic literacy. The research method used is descriptive qualitative. The object of this research is Darussalam Gontor University. The results of this study indicate that Islamic boarding schools in implementing economic literacy carry out several functions; 1) as an educational institution that changes the economic orientation of the community which was originally intended to satisfy wants, to become